Periodontal disease and systemic complications - Rui Vicente Oppermann; Patricia Weidlich; Marta Liliana Musskopf (Sociedade Brasileira de Pesquisa Odontológica, 2012)
Periodontal diseases comprise a number of infectious and inflammatory conditions brought about by the interaction between supragingival and subgingival biofilms and the host inflammatory response. Periodontal diseases should be considered systemic conditions. This means that they are both modulated by the body's systems and play a role as a risk factor for systemic derangements. The current evidence supports some of these interactions, such as smoking as a risk factor for periodontal disease and diabetes mellitus, as both influenced by and influencing inflammatory changes in the periodontal tissue. Other potential associations are still being researched, such as obesity, hormonal changes, cardiovascular disease, and adverse outcomes in pregnancy. These, and others, still require further investigation before the repercussions of periodontal disease can be fully elucidated. Nevertheless, at the present time, the treatment of periodontal diseases-and, most importantly, their prevention-enables adequate intervention as a means of ensuring periodontal health.